A Centralist Approach to Regional Development: The Case of the Russian Ministry for the Development of the Far East. Issue 6 (3rd July 2021) - Libman, Alexander; Yakovlev, Andrei
Abstract: Since 2012, with a view to strengthen the development of strategically important regions, Russia has established several federal agencies responsible for these territories. The essay investigates one of these agencies: the Ministry for the Development of the Far East ( Ministerstvo Rossiiskoi Federatsii po razvitiyu Dal'nego Vostoka ). We identify two main trade-offs associated with the governance approach used in Russia—between federal power and local knowledge, and between bureaucratic expertise and novel ideas—and examine how the ministry has dealt with these trade-offs and their consequences for the ministry's performance.